Theory, synthesis, and characterization of colloidal platinum nanoparticles - Gharibshahi, Elham (2013)
The immense interest in nanoscience nowadays confined within the metal nanoparticles, semiconductor quantum dots, colloids, and clusters of nanoscale dimensions of 1 – 100 nm from the fact that they possess fundamentally discrete electronic states that cause quantum confinement effects of optical, electronic, electrical, and magnetic properties which are substantially different from those of their bulk and useful in technological applications. Metal nanoparticles in particular, exhibit unique optical absorption phenomenon caused by conduction electrons excitation simulated by electromagnetic field of light, which may be described by quantum or classical physics. However, the classical physics models based on Maxwell’s equations deal only with a continuous system and free electrons, thus neglecting the discrete nature of electronic structures of metal nanoparticles. The first objective of the thesis is to establish a new theory of metal nanoparticles based on the intra-band quantum excitation of conduction electrons from the lowest energy states to higher energy states induced by the electromagnetic photon. Metal nanoparticles possess both geometrical and electronic structures, which are thermodynamically stable. The geometrical structure has a minimum isotropic surface energy resulting symmetrically perfect sphere made of Bravais lattice structure. The electronic structure follows the spherical Jellium model and the Thomas-Fermi-Dirac-Weizsacker Model for the density energy functional of conduction electrons at the ground state density satisfying the density functional theory fundamental, where the electron density (r)is the basic quantity. However, using a continuous relationship between the density and absorption, the absorption energy functional is derived and solved numerically using Newton iterative integration method. We simulated the single-band absorption spectra of Al, Ag, Au, and Co nanoparticles of various particle sizes of 4-50 nm and found the conduction band energy decreases sharply with increasing particle size. The agreement between the measured absorption maxima found from literatures and our calculated values encouraged us to extend our simulation for the double-band absorption spectra of Ru, Ce, and Pt nanoparticles at 4 nm size. Two absorption maxima in UV and visible wavelength regions are witnessed but no experimental data in literature worth comparing with our calculation. This led us to the second objective of the thesis, which is to synthesize Pt nanoparticles and exploited the optical absorption results and verify that the theory is applicable also to metal nanoparticles with the double-band absorption spectra. Attempts to produce colloidal Pt nanoparticles with steady absorption spectra previously by various chemical reduction methods often ended up in fast disappearance of the absorption maxima, which open to a speculative interpretation on their optical properties. Stable colloidal Pt nanoparticles were successfully synthesized using the gamma radiolytic method in aqueous solution containing platinum tetraammine chloride (Pt(NH3)4Cl2.H2O) as metal precursor, polyvinyl pyrrolidone (PVP) as capping agent, isopropyl alcohol as radical scavengers of hydrogen and hydroxyl radicals, and tetra hydrofuran and deionized water as solvents for Pt(NH3)4Cl2 and PVP respectively. Nitrogen was bubbled through the homogeneous solutions before they were irradiated with 60Co gamma-rays of different doses without a reducing agent. The synthesized Pt nanoparticles were characterized using XRD, TEM, and UV-visible spectroscopy. The XRD peaks showed the FCC crystalline structure with a lattice parameter of 0.3924 nm. The TEM images confirmed Pt nanoparticles were a spherical shape with the mean particle size decreased from 5.8 to 2.7 nm with increasing dose from 80 to 120 kGy and increased with increasing Pt ions concentration (5.0 - 20.0) × 10-4 M. The synthesized Pt nanoparticles were fully reduced and highly pure demonstrated by steady double-band absorption maxima in the regions of 215 and 265 nm, which blue shifted to lower wavelengths with increasing dose due to decrease of particle size. The absorption maxima originated from the intra-band quantized transitions of conduction electrons of energy state with quantum numbers of {2;5ln or 5d } to higher energy states with quantum numbers of {6n ; 1,0l ; 1,0s} for the absorption maxima of 215 nm and from energy state with quantum numbers {0;6ln or 6s } to higher energy states with quantum numbers of {7n ; 0l ; 0s} for the absorption maxima of 265 nm. To study this possibility, we calculated the absorption spectra of Pt nanoparticles of spherical diameters similar to those obtained from the experiment in the regions from 2.7 to 5.8 nm. We found good agreement between the experimental data of conduction bands and the theoretical conduction bands within less than 1% variance. This suggests that intra-band quantized excitation of conduction electrons can occur in metal nanoparticles and the new theory is fundamentally valid to describe the quantum mechanical absorption phenomenon in metal nanoparticles.